Pengaruh Kepemimpinan Transaksional dan Transpormasional Terhadap Kinerja Karyawan Bamk BPD Bali - Negara, I Wayan Artha; Dewi, A.A Sagung Kartika (E-Jurnal Manajemen; Vol 3 No 12 (2014), 2014)
The purpose of the study was to analyze the effect of competence, physical work environment and motivation on job satisfaction. This study used a population of 64 people which was using a population method and were collected by questionnaire. The results of the study showed that the effect of partially variable competence, physical work environment and motivation on job satisfaction were positive and significant, the effect of variables simultaneously competence, physical work environment and motivation on job satisfaction were positive and significant and the physical work environment was a dominant variable on employee job satisfaction on the CV. Jaya Utama Teknik
Keywords: Dissatisfaction, Complaining Attitude, Complaining Behavior